2019
DOI: 10.1111/apt.15539
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes in inflammatory bowel disease patients treated with vedolizumab, anti‐TNF or conventional therapy: results of the European CONCEIVE study

Abstract: Summary Background Women with inflammatory bowel diseases (IBD) often receive biologicals during pregnancy to maintain disease remission. Data on outcome of vedolizumab‐exposed pregnancies (VDZE) are sparse. Aims To assess pregnancy and child outcomes of VDZE pregnancies and to compare these results to anti‐TNF exposed (TNFE) or both immunomodulatory and biologic unexposed (CON IBD) pregnancies. Methods A retrospective multicentre case‐control observational study was performed. Results VDZE group included 79 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
103
2
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(115 citation statements)
references
References 29 publications
(64 reference statements)
4
103
2
6
Order By: Relevance
“…and 15% (CON-IBD), respectively. Compared with previously published data based on 31 study sites, Moens et al 33 , 35 , 36 reported slightly lower patient numbers, since their analysis was based on only 29 study sites.…”
Section: Resultscontrasting
confidence: 57%
See 4 more Smart Citations
“…and 15% (CON-IBD), respectively. Compared with previously published data based on 31 study sites, Moens et al 33 , 35 , 36 reported slightly lower patient numbers, since their analysis was based on only 29 study sites.…”
Section: Resultscontrasting
confidence: 57%
“…In the work by Moens et al , median birth weight did not differ between the groups (VDZ, anti-TNF, immunomodulatory/biologic-naïve). 35 Congenital anomalies were reported for 5% (VDZ-exposed), 2% (TNF-exposed), and 2% (CON-IBD) of the observed cases, whereas serious infections during the first year of life were documented in 5% (VDZ-exposed), 10% (TNF-exposed), and 12% (CON-IBD) of the cases.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations